2022
DOI: 10.1177/00224871221121767
|View full text |Cite
|
Sign up to set email alerts
|

Preparing in Advance to Respond in-the-Moment: Investigating Parallel Changes in Planning and Enactment in Teacher Professional Development

Abstract: Despite warrants for classroom discussion, research consistently finds that discussions in K-12 classrooms remain rare. Our research investigates whether and in what ways practice-based teacher learning opportunities focused on discussion facilitation influence opportunities for student talk. Grounded in data from a job-embedded professional development program for fourth- to eighth-grade literacy teachers, we analyzed videos of teachers co-planning and co-facilitating discussions with students. Findings indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Adoption of this approach does not negate a focus on developing responsive and adaptive teaching that recognises the intentional, situated and contextual aspects of teaching [40][41][42]88]. A number of authors have suggested, however, that the inclusion of AoPs and rehearsals in coursework can support the development of routines, responsive teaching and adaptive expertise [12,23,32,36,44,89,90].…”
Section: Selecting Implementing and Evaluating Core Practicesmentioning
confidence: 99%
“…Adoption of this approach does not negate a focus on developing responsive and adaptive teaching that recognises the intentional, situated and contextual aspects of teaching [40][41][42]88]. A number of authors have suggested, however, that the inclusion of AoPs and rehearsals in coursework can support the development of routines, responsive teaching and adaptive expertise [12,23,32,36,44,89,90].…”
Section: Selecting Implementing and Evaluating Core Practicesmentioning
confidence: 99%
“…Taken together, the forms of mentoring inside and outside the action represent an integrated repertoire of practices to be used in purposeful and flexible ways to help novices learn to teach. For example, forms of mentoring outside the action, such as co-planning, create opportunities for novices to learn how to design worthwhile learning opportunities (Kavanagh, Danielson et al, 2022; Smith, 2005). Other outside-the-action practices, such as journal writing, video analysis, and debriefing, provide opportunities for novices to develop habits of reflection and self-assessment (Stanulis et al, 2019).…”
Section: Teacher Mentoringmentioning
confidence: 99%